Why invest in Research & Development for sorghum and millets? The business case for East and Southern Africa - Orr, A.; Schipmann-Schwarze, C.; Gierend, A.; Nedumaran, S.; Mwema, C.; Muange, E.; Manyasa, E.; Ojulong, H. (Elsevier, 2020)
This article synthesizes recent research by ICRISAT and its partners to analyse the business case for sorghum and millets in ESA and the wider strategy of commercialization on which this is based. The business case is stronger for sorghum because of its greater impact on poverty and food security, but millets are better suited to a strategy of commercialization. Commercial demand for millets is primarily driven by specialty markets for flour while that for sorghum is limited to beer. Demand for improved varieties is driven primarily by the need for early – maturity that shortens the hungry period. Future growth in production depends on increased opportunities for inter-regional trade.